Prognostic nutritional index predicts staging and mortality in cardiovascular-kidney-metabolic syndrome - Yiying Liu; Fuyuan Zhang; Ruikang Liu; Jun Li; Cong Chen; Xuanchun Huang; Yulian Yuan; Chao Meng; Xiao Xia; Yonghao Li (PLoS ONE, 2025)
Background Cardiovascular-kidney-metabolic syndrome (CKM) is a multisystem disorder involving cardiovascular, kidney, and metabolic diseases, associated with high mortality risk. The prognostic nutritional index (PNI), reflecting nutritional and immune status, predicts outcomes in various diseases. This study evaluates PNI’s association with CKM stages and mortality. Methods Data from 10,448 CKM patients in the 1999–2018 NHANES cohort were analyzed. Weighted logistic regression assessed PNI’s relation to CKM stages. Nonlinear relationships were explored via restricted cubic spline and two-piecewise linear regression. Kaplan-Meier and Cox models examined PNI’s association with all-cause and cardiovascular mortality. Subgroup analyses explored interactions with demographic and clinical factors. Significance was set at P < 0.05. Results PNI was highest in CKM stage 0 and lowest in stage 4 (53.52 ± 0.16 vs. 51.54 ± 0.25, P < 0.001). Notably, an inverted U-shaped relationship was identified for early stages (0–1), while an inverse association was observed for stage 4 and advanced CKM. Over a median 123-month follow-up, the highest PNI quartile had superior survival for all-cause (83.63% vs. 52.58%, P < 0.001) and cardiovascular mortality (95.69% vs. 88.18%, P < 0.001). PNI was inversely correlated with mortality risk, with specific thresholds observed at 50 for all-cause mortality and 51 for cardiovascular mortality. This association was modified by gender, race, and BMI. Conclusion PNI is significantly associated with both early and advanced stages of CKM. PNI serves as an independent predictor for all-cause and cardiovascular mortality in CKM patients.